DIABETES AND HYPERTENSION: AN EXAMPLE OF COMMUNITY AWARENESS IN THE CAPITAL (Turkey Health Literacy Journal, 2024)
Noncommunicable diseases affect people of all walks of life, all over the world, of all ages, with devastating health consequences for individuals and communities. Hypertension and diabetes are among the most common causes of death and disease all over the world, which are among the leading noncommunicable diseases that are rapidly increasing in incidence and especially affecting low and middle-income societies in the world. The prevalence of hypertension in adults in Turkey is reported as 31.8%. This cross-sectional-descriptive study was conducted to determine the hypertension and diabetes risk factors of individuals who participated in community-based studies carried out to increase awareness of hypertension and diabetes in all districts of Ankara. Data of 2460 people aged 18 and over who participated in the study were examined. The research data were statistically analyzed with the IBM Statistics22.0 SPSS package program. The mean age of the participants in the study was 47.6±14.6. While blood pressure was found to be normal in 60.8% of the blood pressure arterial measurements, instant blood glucose measurements were found in 6.7% of them. Blood sugar and blood pressure were found to be significantly higher in obese individuals. This situation reveals once again that obesity is a significant risk for high blood sugar and high blood pressure. As a result, blood pressure and blood glucose measurements provided at the stands can be an important step for early diagnosis and treatment and can help individuals become conscious about their own health conditions. Considering the importance and impact of community-based studies in the fight against hypertension and diabetes, it is important to conduct more comprehensive and targeted studies.